California State College at Hayward [Bulletin] Summer Session 1964 - California State College at Hayward:::::: (California State College at Hayward; California State Printing Office, 1964)
A catalog of courses offered by California State College at Hayward for the summer session of 1964. Includes academic calendar, names of faculty and administrators, and descriptions of courses and workshops offered.